„Jak to się stało, że masz syna z nowym Bondem?” – kobiece, męskie i boskie w poezji Justyny Bargielskiej - Fazan, Jarosław (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The paper applies to the work of one of the most important Polish writers of the last decade. Bargielska combines bold poetic experiments with a keen testimony of an ordinary life of a young woman, who experiences life in the beginning of the 21st century in Poland. On the one hand, the poet declares a conservative worldview (her value system is based on the “trinity”: Catholicism, heterosexuality, motherhood), on the other hand, she brutally and mercilessly uncovers the subjugation of a woman in the world of a male-dominated language. Her writing deconstructs this system, as it discovers the literature as a space for the practice of personal freedom beyond the slogans and ideological divisions; she manages to create her own independent form of existence. The poet renews feminine way of being through the deconstruction of religious myths and cultural stereotypes, confronted with the physiological and social reality.